The Desirability of Jewish Conversion to Christianity in Contemporary Catholic Thought - Gregerman, Adam (Horizons, 2018)
I argue that the authors of the December 2015 Vatican statement "The Gifts and the Calling of God Are Irrevocable" both present the Jewish Old Covenant as a good covenant (rejecting traditional Christian supersessionism) and nonetheless view Jews' conversion to the better Christian New Covenant as desirable. I challenge the assumption that post-Nostra Aetate positive views of the Jewish covenant, including the claim that Jews are already "saved," preclude a desire for Jews to convert to Christianity. On the contrary, I show that the authors' claim that the New Covenant is the "fulfillment" of the Old Covenant provides a motive for contemporary Christians to emulate the efforts made by those early followers of Jesus who shared the gospel with their fellow Jews. To support my argument, I first carefully study the writings of Cardinal Walter Kasper. The authors of Gifts draw almost entirely on Kasper's nuanced and complex views regarding the desirability of Jewish conversion to Christianity, adopting even his approach to and format for presenting this controversial claim.